Pengaruh Dewan Direksi, Komisaris Independen, Komite Audit, Kepemilikan Manajerial dan Kepemilikan Institusional Terhadap Kinerja Keuangan - FRANSISCA W, MARIA FRANSISCA (Jurnal Ilmu Manajemen (JIM), 2013)
This study aims to examine the effect of board of director, independent commissioner, audit committee, managerial ownership, and institutional ownership on financial performance proxied by market value added (MVA). The study was based on 54 property and real estate companies listed in Indonesian Stock Exchange from 2008-2011. By using purposive sampling technique, the sample is obtained by 15 companies. Data used in this research were obtained from annual financial report and IDX Statistic through the website of IDX. The data analysis technique used in this study is multiple linear regresision analysis. The results show that simultaneously board of director, independent commissioner, audit committee, managerial ownership, and institutional ownership have significant effect on financial performance. The t-test results show that partially independent commissioner and institutional ownership have positive significant effect on financial performance. Board of director, audit committee, and managerial ownership have no significant effect on financial performance. Keywords: independent commissioner, audit committee, managerial ownership, institutional ownership, financial performance.